Bacteria serve up a tasty solution to the global plastic problem. (23rd December 2021) - Sadler, Joanna C.; Wallace, Stephen; Robertson, Marie-Anne
Abstract : Rattling around on a cold, damp Edinburgh street, a plastic water bottle is a stark reminder of one of the greatest environmental crises facing our planet. In little under 100 years a growing tsunami of plastic waste has contaminated not just our streets but nearly every corner of the natural world – from Mount Everest to the deepest oceans. But this plastic bottle provided the inspiration that could yet turn the tide. Diverted from landfill to the laboratory the bottle soon grabbed the attention of the world's media by undergoing a remarkable transformation from plastic into vanillin – the main component of vanilla and one of the most in-demand spices in the world. This seemingly impossible act of alchemy was made possible by harnessing the metabolic power of bacteria. Its success has enormous implications. Not only could it meet our insatiable appetite for this rare flavouring, but it could radically change the way we tackle another addiction – the endless stream of single-use and disposable plastics that have become part of everyday life. Yet this only scratches the surface of the potential of this approach. By coaxing microbes to behave as eco-friendly factories that produce useful materials, we could tackle many other global challenges.